2018
DOI: 10.5812/msnj.86309
|View full text |Cite
|
Sign up to set email alerts
|

Severe Maternal Outcomes in a Tertiary Referral Teaching Hospital in Sistan and Baluchistan Province, Iran: A Cross Sectional Study

Abstract: Background: Since maternal near miss (MNM) could act as a surrogate of maternal death, the implementation of MNM audit at hospital level can provide an opportunity to study maternal morbidity at a large scale. Objectives: The current study aimed at investigating severe maternal outcomes (SMO; i.e. MNM + maternal death [MD]) in a referral hospital. Methods: A prospective, facility-based, cross sectional study was conducted from 22 June to 22 December 2017. The current study was performed in a tertiary referral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Gravidity and Parity were also identified as independent determinants of maternal near miss, as multigravid and multiparous women were more likely to experience a maternal near miss condition. Similar observations were made in South Sudan, Western Ethiopia, Northern Ethiopia, Iran, and India [15,19,[21][22][23]. Hence, there may be a need to increase awareness, broaden access and overcome known barriers to family planning services, to limit the number of pregnancies, thereby reducing near miss morbidities.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Gravidity and Parity were also identified as independent determinants of maternal near miss, as multigravid and multiparous women were more likely to experience a maternal near miss condition. Similar observations were made in South Sudan, Western Ethiopia, Northern Ethiopia, Iran, and India [15,19,[21][22][23]. Hence, there may be a need to increase awareness, broaden access and overcome known barriers to family planning services, to limit the number of pregnancies, thereby reducing near miss morbidities.…”
Section: Discussionsupporting
confidence: 54%
“…Human immunodeficiency virus (HIV/AIDS) infection, tuberculosis, anaemia, and cardiac disease in pregnancy are examples of indirect causes [7,9,11,12]. Studies have shown that the predictors of maternal near miss are advanced maternal age, race, illiteracy, polygamous family, low socioeconomic status, rural residency, fewer or no antenatal care (ANC) follow-up, multiple pregnancies, high parity, previous caesarean delivery, caesarean delivery in the current pregnancy, pre-existing medical conditions, lack of referral, lack of insurance coverage, anaemia, and extremes of body weight [5,[13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%